2022
DOI: 10.21037/tcr-22-653
|View full text |Cite
|
Sign up to set email alerts
|

Construction of miRNA-mRNA network and a nomogram model of prognostic analysis for prostate cancer

Abstract: Background: Dysregulated genetic factors correlate with carcinoma progression. However, the hub miRNAs-mRNAs related to biochemical recurrence in prostate cancer remain unclear. We aim to identify potential miRNA-mRNA regulatory network and hub genes in prostate cancer.Methods: Datasets of gene expression microarray were downloaded from Gene Expression Omnibus (GEO) database for Robust Rank Aggregation (RRA), targeted gene prediction, gene function and signal pathway enrichment analyses, miRNA-mRNA regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In another study, researchers constructed a miRNA-mRNA regulatory network containing miR-106b-5p to identify genes such as TMEM100, FRMD6, NBL1, and STARD4 for the diagnosis and prognosis of prostate cancer patients. They concluded that signaling pathways such as cGMP-PKG, PI3K-Akt, and cAMP are involved in regulating prostate cancer progression ( Su et al, 2022 ). Among the five single miRNAs studied, miR-106b-5p demonstrated the best diagnostic ability, exhibiting excellent sensitivity and specificity (90.48% and 63.10%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, researchers constructed a miRNA-mRNA regulatory network containing miR-106b-5p to identify genes such as TMEM100, FRMD6, NBL1, and STARD4 for the diagnosis and prognosis of prostate cancer patients. They concluded that signaling pathways such as cGMP-PKG, PI3K-Akt, and cAMP are involved in regulating prostate cancer progression ( Su et al, 2022 ). Among the five single miRNAs studied, miR-106b-5p demonstrated the best diagnostic ability, exhibiting excellent sensitivity and specificity (90.48% and 63.10%, respectively).…”
Section: Discussionmentioning
confidence: 99%